Students’ Satisfaction of Online Learning During COVID-19 Pandemic - Silvani Safitri; Sriati Usman; Abdul Kamaruddin; Anshari Syafar; Aminah (Jurnal Kreatif Online, 2021)
This research aims to find out the students' satisfaction of online learning and the factors that affect the students’ satisfaction of online learning during the COVID-19 Pandemic at Tadulako University in the academic year 2020/2021. This research used qualitative approach. This research collected the data through survey method using a questionnaire and interview. The research subject was the third year students of the English Language Education program at Tadulako University in the academic year 2020/2021. The samples were selected using purposive sampling to choose the students as the respondents. The result indicated that the students' satisfaction of online learning during the COVID-19 Pandemic is 62.13%, which wasconsidered satisfied. Percentages for each factor were described as follow; 66.37% or equivalent as satisfied for Student-Lecturer Interaction, 67.64%or equivalent as satisfied for Instructional Materials, 61.95% for Online Learning Platformor equivalent as satisfied, and 51,54% for Functionality or equivalent as dissatisfied. So, three factors are satisfied, and one factor is dissatisfied. The result stated as 'satisfied' dominates the result of the students' responses; it can simply conclude that those factors affect the students' satisfaction of online learning during the COVID-19 Pandemic.